Multi-criteria performance optimization and analysis of a gas-steam combined power system - Gonca, Guven; Bashan, Veysi (SPRINGER HEIDELBERG, 2019)
This paper reports a comprehensive investigation of performances for a gas-steam combined power system (GSCPS) by considering exergy and thermo-ecology criteria. The most known and important parameters such as power density, power output, exergy destruction, exergetic efficiency, ecological coefficient performance (ECOP) and effective ecological power density (EFECPOD) are investigated. The influences of turbine design parameters such as turbine speed, mass flow rate of the working fluid, pressure ratio, equivalence ratio, intake air temperatures and pressures, residual gas fraction, fluid temperatures in heat exchanger, the pressure of high-pressure steam turbine, the pressure of medium-pressure steam turbine, the pressure of low-pressure steam turbine, the pressure of open feedwater heater, the pressure of condenser on the performance specifications have been evaluated. The results indicated that the component properties have remarkable impacts on the performance parameters of the GSCPS.
Keywords: Gas-steam combined power system; Thermo-ecology; ECOP; Exergy; EFECPOD; SPARK-IGNITION ENGINE; IRREVERSIBLE MILLER CYCLE; EXERGY ANALYSIS; THERMODYNAMIC ANALYSIS; BRAYTON-CYCLE; REGENERATIVE BRAYTON; EXERGOECONOMIC ANALYSIS; ECONOMIC-ANALYSES; RANKINE CYCLES; TURBINE CYCLE; Engineering